2012
DOI: 10.1128/jcm.00029-12
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir-Resistant Cytomegalovirus (CMV) Retinitis in a Patient with Wild-Type CMV in Her Plasma

Abstract: A patient with systemic cytomegalovirus (CMV), including chorioretinitis, received localized and systemic ganciclovir, systemic cidofovir analog, and localized foscarnet. Mutations conferring ganciclovir and cidofovir resistance were detected in CMV from the aqueous fluid but not in CMV from plasma. Quantifying CMV from aqueous fluid was valuable for monitoring the clinical response and predicting resistance. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In most instances, the more severe inflammation and vascular occlusion was ascribed to relative retention of anti-CMV immunoreactivity. However, other studies have failed to identify consistent difference in clinical presentation based on HIV status [ 18 20 , 24 , 26 , 30 33 , 37 40 , 44 , 94 , 95 ]. In our review, of all the reported cases to date of HIV-negative CMVR not associated with Good syndrome or following intraocular or periocular administration of corticosteroids, clinical features of the inflammation were reported in 199 of the 248 eyes (80.2 %).…”
Section: Reviewmentioning
confidence: 99%
“…In most instances, the more severe inflammation and vascular occlusion was ascribed to relative retention of anti-CMV immunoreactivity. However, other studies have failed to identify consistent difference in clinical presentation based on HIV status [ 18 20 , 24 , 26 , 30 33 , 37 40 , 44 , 94 , 95 ]. In our review, of all the reported cases to date of HIV-negative CMVR not associated with Good syndrome or following intraocular or periocular administration of corticosteroids, clinical features of the inflammation were reported in 199 of the 248 eyes (80.2 %).…”
Section: Reviewmentioning
confidence: 99%
“…A 39-year-old female with Burkitt's lymphoma on RHyperCVAD developed CMV retinitis and was treated with intravenous ganciclovir, intravitreal ganciclovir, and intravenous foscarnet. [5] Another 50-year-old man with T-cell ALL developed CMV retinitis during 4 th cycle of R HyperCVAD and was treated with oral valganciclovir. [6] A 49-year-old man with ALL, on salvage chemotherapy with HyperCVAD, developed CMV retinitis and was treated with intravenous ganciclovir with preservation of visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…First‐line therapy is IV ganciclovir or its prodrug valganciclovir which can be given orally and has comparable efficacy . In cases that are refractory to ganciclovir or valganciclovir, or in those who are unable to tolerate them due to toxicity, IV foscarnet is recommended before IV cidofovir . Probenecid pre‐ and post‐infusion of cidofovir is required for nephroprotection.…”
Section: Treatmentmentioning
confidence: 99%
“…131,[135][136][137] In cases that are refractory to ganciclovir or valganciclovir, or in those who are unable to tolerate them due to toxicity, IV foscarnet is recommended before IV cidofovir. 137,138 Probenecid pre-and post-infusion of cidofovir is required for nephroprotection. Cidofovir can also cause hypotony in the presence of a ganciclovir implant.…”
Section: Treatmentmentioning
confidence: 99%